Secondary Publication: Molecularly Targeted Therapeutic Drug Treatment in Gastroenterology - Junko Tahara (Tokyo Women's Medical University Journal, 2023)
Molecularly targeted drugs affect various molecules associated with cancer cell progression, infiltration, and metastasis. Recent advances in molecular biology have identified molecules associated with cancer and inflammatory disease, leading to the development of new molecularly targeted drugs. Unlike cytotoxic anticancer agents, molecularly targeted drugs act on cancer-specific molecules and cause less damage to normal cells. Consequently, there are fewer adverse events associated with molecularly targeted drugs. These advances in drug development promise novel and effective treatments for gastroenterological diseases. This article is based on a study first reported in the Journal of Tokyo Women's Medical University (in Japanese), 2022; 92 (5):153-7.